Moving Towards Universal Health Coverage in Haiti - Ken Hashimoto (Health Systems & Reform, 2020)
Haiti announced in 2018 its aim to achieve universal health coverage. In this paper, we discuss what this objective means for the country and what next steps should be taken. To contextualize the notion, we framed Haiti en route to the 2030 goal and analyzed qualitatively the status quo in terms of geographic, financial, and service access. For each dimension, we focused on the context, the government’s policies and political agendas, their implementation progress, and key influential factors. Our analysis found little progress and numerous challenges. Geographic access was limited due principally to the insufficient number of facilities, difficulties in reaching health facilities, and local customs. Financial coverage was low because of the government’s insufficient budgets, inefficient budget allocation, and ineffective management. Service access also had room for significant improvement for a lack of basic infrastructure and resources, gaps between the essential service package guidelines, health professionals’ skills, and the needs, as well as deficiencies in people-centered care. These factors affected not only health service coverage but also its quality. We found that the root causes of these issues were composed of unstable financing mechanisms, opportunistic resource allocation, and ineffective management control systems. We suggest that to overcome these issues and achieve universal health coverage with decent service quality, Haiti’s health system needs to be reformed by implementing strategic financing, decentralized management systems, and community engagement in primary health care.